2020
DOI: 10.3389/fsoc.2020.587024
|View full text |Cite|
|
Sign up to set email alerts
|

Sport Karate and the Pursuit of Wellness: A Participant Observation Study of a dojo in Scotland

Abstract: Health problems in society are numerous, not least stress and stress-related illness. Physical activities, including martial arts, are increasingly viewed as a means of managing such risks to health. While there are forms of karate that have a philosophical and meditative character that is related to spiritual wellness, karate as a competitive sport is less likely to be thought of in this light. The purpose of this paper is to present through a participant observation study the representations that karateka of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Benefits include physical and psychological aspects, including reducing negative emotional reactions, improving balance, and improving cardiovascular and musculoskeletal fitness. [10][11][12] However, there is no evidence of the effectiveness of karate in cancer patients after therapy on QoL and on other outcomes related to cancer disease. To date, this is the first quasi-experimental study aimed at evaluating the effectiveness of karate in improving QoL (primary outcome), anxiety, depression, sleep quality, and multidimensional psychosomatic symptoms (secondary outcomes) in oncology patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits include physical and psychological aspects, including reducing negative emotional reactions, improving balance, and improving cardiovascular and musculoskeletal fitness. [10][11][12] However, there is no evidence of the effectiveness of karate in cancer patients after therapy on QoL and on other outcomes related to cancer disease. To date, this is the first quasi-experimental study aimed at evaluating the effectiveness of karate in improving QoL (primary outcome), anxiety, depression, sleep quality, and multidimensional psychosomatic symptoms (secondary outcomes) in oncology patients.…”
Section: Introductionmentioning
confidence: 99%
“…Karate represents a physical, mental, and spiritual practice that has been shown to offer a variety of physical and psychological benefits, in addition to possessing a rich history and a rooted tradition. Benefits include physical and psychological aspects, including reducing negative emotional reactions, improving balance, and improving cardiovascular and musculoskeletal fitness 10-12. However, there is no evidence of the effectiveness of karate in cancer patients after therapy on QoL and on other outcomes related to cancer disease.…”
Section: Introductionmentioning
confidence: 99%
“…Social culture and beliefs differ according to the structure of the individual and the sport he/she does (Roychowdhury, 2019). It has been reported that the athletes involved in team sports are strengthened spiritually by establishing a deep sense of bond with their teams, and the sense of habit and beliefs created by sports contribute positively to the mental health of the athletes (Bopp et al, 2021;Turelli, Tejero-González, Vaz and Kirk, 2020). Some team athletes have some beliefs such as wearing the same jersey they won matches, kissing or hitting the ball to the floor several times before serving, etc.…”
Section: Introductionmentioning
confidence: 99%